Coupling Characteristics of Selective-Infiltration-Based Locally Tapered Photonic Crystal Fiber - Hu Liang; Zhi Wang; Yange Liu; Hongye Li; Hongwei Zhang (IEEE Photonics Journal)
We have proposed and experimentally demonstrated a novel compound structure based on selectively infiltrating of a local tapered photonic crystal fiber (TPCF). Theoretical and experimental investigations indicate that tapering photonic crystal fiber (PCF) can change the material refractive index (RI) of silica core, and the RI change can be revealed and proved to influence the effective RI curve of the PCF core mode, which results in the shifting of the phase matching point. Moreover, strong coupling can occur in the infiltrated TPCF due to the increased overlap integral of the involved coupled modes. As application, the proposed configuration based on TPCF has huge potential use in microfluidic, RI, and dual-parameter sensing with high sensitivity, such as ultrahigh strain sensitivity of –139.78 nm/N (–167.74 pm/μϵ).